CAUSES OF RENAL PATHOLOGY IN NEWBORN - Karimdzhanov I.A; Yakhyaeva K.Z (Scholar Express Journals, 2022)
The growth of diseases of the urinary system in newborns in recent years is associated with the influence of environmental factors. In addition, it is unsafe for the unborn child to prescribe antibiotics and a number of other drugs and polypharmacy in the treatment of pregnant women, exposure to various chemical agents that enter the body with air or food. It has been established that the incidence of nephropathy in children from families with kidney pathology is 20 times higher than in the general population. Hence, an ecological and family approach to the early detection of kidney disease in infants is important
Keywords: Newborn; mother; ecology; medical history; kidney pathology.